Pre-1.91 Ga deformation and metamorphism in the Palaeoproterozoic Vammala Migmatite Belt, southern Finland, and implications for Svecofennian tectonics - R.W.R. Rutland; I.S. Williams; K. Korsman (Bulletin of the Geological Society of Finland, 2004)
A metamorphic event in the Vammala Migmatite Belt (VMB) at ~1.92 Ga, revealed by SHRIMP U-Pb analyses of both zircon overgrowths and monazite, is interpreted as post-depositional and is correlated with the development of the early high-grade schistosity. Neither this Early Svecofennian deformation and metamorphism, nor the associated complex folding, is present in the overlying Tampere Schist Belt (TSB) sequence, consistent with the VMB being part of a pre-1.91 Ga basement complex. The ~1.92 Ga event provides a maximum deposition age for the TSB, confirming earlier age estimates. Earlier stratigraphic correlations between parts of the VMB and TSB, and associated tectonic interpretations, can no longer be sustained. The crustal thickening seen in the VMB, and previously attributed to arc accretion at ~1.89 Ga, is now attributed to accretion of a large Svionian marginal basin during the 'Early Svecofennian' orogenic phase at ~1.92 Ga. This is of similar age to the deformation and metamorphism associated with collision in the Lapland-Kola Orogen to the north of the Karelian Province. The well-known post-TSB orogenic phase was also identified in the VMB by a monazite age of 1881 ±6 Ma. A granitoid intrusion gave an emplacement age of 1888 ±5 Ma, comparable to the age of granitoid clasts in the upper part of the TSB succession. The detrital zircon data are interpreted to suggest that deposition of the precursor VMB sediments probably took place soon after an earlier pre-depositional metamorphism at ~1.98 Ga, which affected igneous source complexes dated at ~1.99 Ga and ~2.01 Ga. Mafic rocks in the southern part of the VMB, and probably also the Haveri basalts, represent a renewed episode of extensional magmatism, which might correlate with the 1.96-1.95 Ga Jormua and Outokumpu ophiolites. A pre-1.96 Ga older stage basin has an expression in Sweden and complexes of similar age occur in the concealed Palaeoproterozoic basement south of the Gulf of Finland. Similar rocks, deformed and metamorphosed before ~1.96 Ga, might be present beneath the Central Finland granitoid complex and the late Svecofennian granite-migmatite zone, and were possibly more local sources for both the younger stage Svionian basin sediments and the post-1.91 Ga Bothnian Basin sediments. The TSB and other post-accretionary volcanic sequences, and the associated plutonism, are interpreted to reflect a ~40 m.y. extensional period, inboard of the contemporaneous active margin, between orogenic phases at ~1.92 Ga and ~1.88 Ga. This interpretation provides a more satisfactory explanation of the major heat input to the crust over a very wide area than does the arc accretion hypothesis. The tectonic evolution of the Svecofennian Province has strong similarities to that of the Palaeozoic Lachlan Fold Belt in eastern Australia.